2005
DOI: 10.1021/ac0480949
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characterization of the Charge State and Residue Dependence of Low-Energy CID Peptide Dissociation Patterns

Abstract: Data mining was performed on 28 330 unique peptide tandem mass spectra for which sequences were assigned with high confidence. By dividing the spectra into different sets based on structural features and charge states of the corresponding peptides, chemical interactions involved in promoting specific cleavage patterns in gas-phase peptides were characterized. Pairwise fragmentation maps describing cleavages at all Xxx-Zzz residue combinations for b and y ions reveal that the difference in basicity between Arg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
301
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(325 citation statements)
references
References 30 publications
21
301
0
Order By: Relevance
“…Note also that for the singly charged peptides in which the proton is expected to be localized on the C-terminal basic residue, E 1/2 values follow the same order as their gas-phase proton affinities, a trend consistent with the "mobile proton hypothesis" [2]. For H, K, and R the proton affinities are 988, 996, and 1051 kJ mol Ϫ1 [12], respectively, while the corresponding E 1/2 values are 36.5, 39.4, and 48.8 ( Table 1).…”
Section: Comparison Of Neutral Losses From N-terminal Glutamine To Frsupporting
confidence: 62%
See 1 more Smart Citation
“…Note also that for the singly charged peptides in which the proton is expected to be localized on the C-terminal basic residue, E 1/2 values follow the same order as their gas-phase proton affinities, a trend consistent with the "mobile proton hypothesis" [2]. For H, K, and R the proton affinities are 988, 996, and 1051 kJ mol Ϫ1 [12], respectively, while the corresponding E 1/2 values are 36.5, 39.4, and 48.8 ( Table 1).…”
Section: Comparison Of Neutral Losses From N-terminal Glutamine To Frsupporting
confidence: 62%
“…However, relative abundances of these ions and ions derived from them are not generally used for this process, despite the fact that they can carry additional sequence-specific information. The development of a sound basis for interpreting abundances can therefore be expected to aid peptide identification algorithms and has motivated the work of several laboratories [1][2][3][4][5][6][7]. It is also the motivation of the present work, which examines a highly specific fragmentation process, the "neutral loss" of ammonia and water from a glutamine residue at the amino terminus of a peptide.…”
mentioning
confidence: 99%
“…In traditional sequence search methods, because the expected fragment-ion peak intensities are not known and not easily predicted, they are often simply ignored or given an ad-hoc value based on the ion type. This fails to take into account that the peak intensities are strong functions of the peptide sequence and the charge state, as has been reported in numerous publications [38][39][40]. Moreover, spectral searching needs no assumption on what fragment ions one should expect to see in the MS/MS spectra; it simply gathers similarity information from all peaks, assigned or not, that are consistently present in many experimentally observed spectra.…”
Section: Advantages Of Spectral Searchingmentioning
confidence: 99%
“…While many fundamental studies and statistical analyses have examined the influence of amino acid content on the gas-phase dissociation of unmodified peptides [25][26][27][28][29], no similar work to date has been performed for crosslinked peptides. It has been shown that certain amino acids, including aspartic acid and proline, enhance or promote specific backbone cleavage of peptides [30 -38].…”
mentioning
confidence: 99%